Odontogenic Myxoma Associated to Unerupted Mandibular Molar in a Pediatric Patient: A New Case Description with Comprehensive Literature Analysis - Marta Forte; Giuseppe D’Albis; Antonio d’Amati; Giuseppe Ingravallo; Luisa Limongelli; Gianfranco Favia; Adriano Di Grigoli; Anna Montaruli; Daniela Di Venere; Massimo Corsalini; Saverio Capodiferro (Children)
Background/Objectives: Odontogenic tumors in pediatric patients are uncommon; among all, the intraosseous occurrence of odontogenic myxoma is very rare, accounting for almost 8.5–11.6% of all odontogenic tumors in children. The radiological appearance is highly variable and is often responsible for the diagnostic delay and treatment. Methods: We report a case of odontogenic myxoma occurring in the posterior mandible of a 12-year-old female, found on a panoramic radiograph performed for the delayed eruption of the second inferior molar, treated by conservative surgery. A comprehensive analysis of the literature was also carried out. Results: The radiological features of the presented case were unique, as the lesion was encompassed within the uncompleted (developing) dental crown still unerupted, as confirmed by the macroscopic appearance. Then, the differential diagnosis included odontogenic fibroma, immature dental pulp or follicle from a developing tooth, and ameloblastic fibrodontoma. The histological examination led to the final diagnosis of odontogenic myxoma. As for the literature analysis, after a PRISMA-based selection of the papers, a total of 23 articles (case reports and case series on odontogenic myxomas in pediatric patients, a total of 33 cases) were finally selected and studied; all the pertinent data are widely discussed within the paper. Conclusions: The current case highlights the importance of the radiological investigation in pediatric patients when a delayed eruption lasts for several months, leading to an early diagnosis necessary to avoid more aggressive surgical therapies and possible recurrence; data from the literature about site of occurrence, sex, age, kind of surgical procedure, and recurrence rate are discussed too.